Realizing soil health for food security in Africa - Snapp, Sieglinde S.; Chamberlin, Jordan; Winowiecki, Leigh A.; Amede, Tilahun; Aynekulu, Ermias; Gameda, Samuel; Herrick, Jeffrey E.; Lal, Rattan; Marenya, Paswel; Nagarajan, Latha; Stewart, Zachary; Vågen, Tor (Springer, 2025)
Dramatic improvements in soil health are necessary to increase agricultural production and reduce crop failures. We provide recommendations for scaling of soil health and fertility management in Africa through practical approaches to prioritization, evidence-based policy and effective extension.